Online platform regulation and investment attractiveness: A look at the EU, the UK and impacts on small open economies - Matthias Bauer; Oscar Du Roy; Vanika Sharma (European Centre for International Political Economy (ECIPE), 2023)
Small trade- and investment-oriented economies like the United Kingdom (UK) should carefully consider whether to regulate online platform services based on presumptions rather than evidence that consumers are being harmed. Flimsily enforced platform regulation can have a chilling effect on investments in business expansion and innovation, particularly in technology-adopting industries. In this policy brief, we argue that access to integrated and internationally traded platform services is increasingly important for a country's investment attractiveness, even more so for smaller countries. Access to advanced technologies and the utilisation of network effects create a virtuous cycle of economic opportunities, investments, value creation, and trade. Discretionary and presumption-based competition enforcement, as adopted in the EU, risks hurting smaller countries in particular. The EU has chosen the path of proscriptive and protective policymaking with the DMA to achieve industrial and trade policy goals rather than defending competition in the Single Market. UK competition policy risks being driven by institutional interests and ideological considerations, which could potentially lead to the adoption of a regulatory landscape that is even more restrictive than that of the EU, undermining Britain's ambitions for economic and innovation leadership.
Keywords: 330; Digitale Plattform; Digitale Dienste; Regulierung; Wettbewerbspolitik; Wirkungsanalyse; Investitionsklima; Kleine offene Volkswirtschaft; EU-Staaten; Großbritannien